Power-velocity characteristics and jumping abilities in male combat athletes - Busko, K. (Human Movement, 2016)
Purpose. The aim of the study was to examine differences in power-velocity characteristics, and the maximal power and height of rise of the body`s centre of mass, measured in the counter-movement jump (CMJ) and the spike jump (SPJ), between judoists, boxers and taekwondo athletes.